Marketing And Business Of "Plastic Flowers" In Kurulu District, Jayawijaya Regency - Tulak, Alber; Mahanani, Anti Uni; Suryani, S. A. (AGRIBEST, 2023)
Jayawijaya Regency is one of the regencies in the province of Papua which has the potential to develop ornamental plants, one of which is "Plastic Flowers". Many local and foreign tourists buy this flower as a souvenir. The aims of this study are: 1) To obtain information and the potential for the development of the "Plastic Flower" agribusiness in Jayawijaya Regency; 2) To find out the income of the "Plastic Flower" farming business in Jayawijaya Regency. The research was conducted in Kurulu District. The time of the research is from June to August 2022. The determination of the research location is purposive. The data collected in this study are in the form of Focus Group Discussion (FGD) and survey methods by conducting interviews, distributing questionnaires, and collecting secondary data (documents) from farmers, business actors, and other stakeholders at the "Bunga Plastik" agribusiness center in Kurulu District. Jayawijaya Regency. Based on the study results, it can be concluded: 1) Information and potential for developing "Plastic Flowers" during the planting season from June to August 2022 is 417 bunches. With a price of Rp. 25,000, revenue of Rp. 10,425,000 is obtained with a production cost of Rp. 3,207,600. Then an income of Rp. 7,217,400 is obtained. "Plastic Flower" has the potential to be developed; 2) R/C ratio analysis which states that the contribution of the total costs incurred to total revenue is 7,91. It means that "Plastic Flower" farming in Kurulu District, Jayawijaya Regency is profitable for farmers.